RETRACTED: Progesterone-Calcitriol Combination Enhanced Cytotoxicity of Cisplatin in Ovarian and Endometrial Cancer Cells In Vitro - Ana Paucarmayta; Hannah Taitz; Latoya McGlorthan; Yovanni Casablanca; G. Larry Maxwell; Kathleen M. Darcy; Viqar Syed (Biomedicines)
Initially, patients that respond to cisplatin (DDP) treatment later relapse and develop chemoresistance. Agents that enhance DDP effectiveness will have a significant impact on cancer treatment. We have shown pronounced inhibitory effects of the progesterone-calcitriol combination on endometrial and ovarian cancer cell growth. Here, we examined whether and how progesterone-calcitriol combination potentiates DDP anti-tumor effects in cancer cells. Ovarian and endometrial cancer cells treated with various concentrations of DDP showed a concentration-dependent decrease in cell proliferation. Concurrent treatment of cells with DDP and progesterone-calcitriol ombination potentiated anticancer effects of DDP compared to DDP-calcitriol, or DDP-progesterone treated groups. The anticancer effects were mediated by increased caspase-3, BAX, and decreased BCL2 and PARP-1 expression in DDP and progesterone-calcitriol combination-treated cells. Stimulation of the PI3K/AKT and MAPK/ERK pathways seen in cancer cells was reduced in DDP-progesterone-calcitriol treated cells. Pretreatment of cells with specific inhibitors further diminished AKT and ERK expression. Furthermore, progesterone-calcitriol potentiated the anti-growth effects of DDP on cancer cells by attenuating the expression of SMAD2/3, multidrug resistance protein- 1 (MDR-1), and ABC transporters (ABCG1, and ABCG2), thereby impeding the efflux of chemo drugs from cancer cells. These results suggest a potential clinical benefit of progesterone-calcitriol combination therapy when used in combination with DDP.